Entrepreneurship Orientation on MSME’s Performance, Competitive Advantage and Innovation Strategies as Mediation - Wicaksono, Muchammad Andrianto; Moko, Wahdiyat; Rofiaty, Rofiaty (International Journal Labs, 2022)
Background: The agriculture industry in Indonesia produces a wide range of goods. Coffee is one of them. One of Indonesia's biggest exports to the rest of the world is coffee. Indonesia, the third-largest producer of coffee worldwide, has acknowledged coffee as a staple good. According to Pertanian.go.id, there are 1.2 million hectares of coffee plantations in Indonesia. Community coffee plantation land makes up 96% of the plantation area, while private firms own the remaining 4%. This demonstrates the importance of smallholder plantings to Indonesia's coffee industry. Aim: This study aims to assess the extent of the implementation of entrepreneurial orientation in plantations and post-harvest processing of coffee commodities through the mediating role of competitive advantage and innovation strategies to improve the performance of MSMEs in the plantation agro-industry and post-harvest coffee in Malang Raya. research methods used survey methods. Method: The data were obtained from questionnaires and necessary documents. Testing using partial Least square (PLS-SEM) and bootstrap. Findings: The findings of this study reveal that entrepreneurial orientation has a positive and significant direct effect on the performance of MSMEs while the role of competitive advantage and innovation strategy as a mediation of entrepreneurial orientation is not able to have a positive and significant influence on the performance of MSMEs in the plantation agro-industry and post-harvest coffee in Malang Raya.